The influence of professionalism on the performance - Syardiansah Syardiansah; Dyah Ayu Ardiyanti; Siska Nurjanah (Faculty of Economics and Business Mulawarman University, 2023)
This study aims to determine how the influence of professionalism on the performance of employees of the Regional Development Planning Agency (BAPPEDA) of Aceh Tamiang Regency. The research method used in this study is a quantitative method. To get the data used observation techniques, interviews and distributing questionnaires. The sources and types of data used are qualitative and quantitative as well as primary and secondary data. The population in this study were 43 BAPPEDA employees, all of whom were sampled using saturated sampling technique. The results of the research that has been processed with the help of SPSS show the results of the linear regression equation, namely Y = 3.791 + 0.421X. The coefficient of determination (R) shows a value of 0.436. And the t sig and F sig values of the professionalism variable show a value of 0.004. From all the results, it can be concluded that professionalism has a positive and significant influence on the performance of the Aceh Tamiang Regency Regional Development Planning Agency (BAPPEDA) employees. 43.6% of the professionalism variable can explain the effect on performance and the remaining 56.4% is influenced by other variables not explained in this study.